ANALYSIS OF BUYING AND SELLING CONTRACTS IN ONLINE FOOD DELIVERY SERVICE TRANSACTIONS GOFOOD, GRABFOOD AND SHOPEEFOOD - Yulistia, Zahrah Nazhifah; Nawawi, M. Kholil; Sutisna, Sutisna (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2023)
The current technological advancements have made it easier for people to buy and sell. Buying and selling activities that used to happen outside the house can now be done from home. Buying and selling activities can be done through various online services widely available today such as GoFood, GrabFood and ShopeeFood, which are online food delivery services. This research aims to analyze the contractual agreements in online food delivery services such as GoFood, GrabFood, and ShopeeFood from the perspective of Islamic Economics. The research adopts a qualitative approach with a descriptive research method. The findings of this research indicate three types of contracts involved in the transactions of GoFood, GrabFood, and ShopeeFood, namely ijarah agreement, wakalah, and buying and selling contracts. This study suggests that the transactions in these three services cannot be fully compliant with Islamic principles if the customers use cash payment methods. Cash payment methods in online food delivery services should be avoided, and it is better to use non-cash payment methods to avoid causing harm to drivers and the risk of engaging in usury (riba).